Exploring INQF-Based Curriculum in English Education Study Programs: Investigation of Curriculum Implementation - Lamhot Naibaho; Mardin Silalahi (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
This study is about implementing the higher education curriculum based on the Indonesian National Qualification Framework (INQF). It was done at Universitas Kristen Indonesia strictly in the English Language Education Study Program. This study aims to find out how the implementation of the higher education curriculum based on INQF is. The study method used was a qualitative study with a descriptive design. The data of the study were collected through interviews. The instrument of the study was the interview sheet. The informants of the study were the head of the Quality Assurance Agency of Universitas Kristen Indonesia, the head of the Faculty Quality Assurance Agency, and the lecturers of the English Language Education Study Program. The data taken through interviews were analyzed descriptively through transcribing the interview data, data reduction, data display, and drawing conclusions. The result of the study is that the implementation of the learned curriculum is found to be through applicable, simple, and appropriate syllabus content, adding new information, and achieving goals and objectives, according to curriculum planning and quality standards. However, it requires improvement in certain parts of the curriculum implementation that some of the lecturers did not adjust the INQF-Based curriculum into the course they taught. Then it is concluded that although the INQF-Based curriculum has been structurally and well organized, it needs to be implemented by the whole lecturers in their learning and teaching. These findings suggest to the leadership of the University through the Quality Assurance Agency to control the implementation of the curriculum both at the Study Program level and at the lecturer level in carrying out the teaching and learning process.